Experimental Investigation of Low Density Sound Insulated Concrete Fabricated Wall Cladding Tiles. Issue 6 (August 2020) - Pradeep, S; Karthikeyan, R; Rajmohan, N
Abstract: The growing demand for the need of sound insulation in buildings such as hospitals, recreational institutions and religious buildings is rising in recent years. The material used should be of highly sound insulated as well as easy to install. In this study light weight concrete is used as Wall Cladding tiles in the building, as light weight concrete shows satisfactory sound insulation property. The light weight Wall cladding was fabricated by addition of Fiber glass powder and alccofine as a cement replacement and different sizes of Cenosphere such as Cenosphere 300 micron and Cenosphere 425 micron as a fine aggregate replacement. Various parameters of the light weight concrete Wall Cladding tile both physical and mechanical properties were investigated. The test were conducted to determine the compressive strength, and the sound insulation ability of the fabricated Wall Cladding tile. The experimental investigation shows that Wall Cladding fabricated as a light weight concrete has reliable compressive strength of 6.5 N/mm 2 and satisfactory sound insulation property.